Vestiges of the Bacterial Signal Recognition Particle-Based Protein Targeting in Mitochondria - Pyrih, Jan; Pánek, Tomáš; Durante, Ignacio Miguel; Rašková, Vendula; Cimrhanzlová, Kristýna; Kriegová, Eva; Tsaousis, Anastasios D; Eliáš, Marek; Lukeš, Julius (Molecular biology and evolution, 2021)
The main bacterial pathway for inserting proteins into the plasma membrane relies on the signal recognition particle (SRP), composed of the Ffh protein and an associated RNA component, and the SRP-docking protein FtsY. Eukaryotes use an equivalent system of archaeal origin to deliver proteins into the endoplasmic reticulum, whereas a bacteria-derived SRP and FtsY function in the plastid. Here we report on the presence of homologs of the bacterial Ffh and FtsY proteins in various unrelated plastid-lacking unicellular eukaryotes, namely Heterolobosea, Alveida, Goniomonas, and Hemimastigophora. The monophyly of novel eukaryotic Ffh and FtsY groups, predicted mitochondrial localization experimentally confirmed for Naegleria gruberi, and a strong alphaproteobacterial affinity of the Ffh group, collectively suggest that they constitute parts of an ancestral mitochondrial signal peptide-based protein-targeting system inherited from the last eukaryotic common ancestor, but lost from the majority of extant eukaryotes. The ability of putative signal peptides, predicted in a subset of mitochondrial-encoded N. gruberi proteins, to target a reporter fluorescent protein into the endoplasmic reticulum of Trypanosoma brucei, likely through their interaction with the cytosolic SRP, provided further support for this notion. We also illustrate that known mitochondrial ribosome-interacting proteins implicated in membrane protein targeting in opisthokonts (Mba1, Mdm38, and Mrx15) are broadly conserved in eukaryotes and nonredundant with the mitochondrial SRP system. Finally, we identified a novel mitochondrial protein (MAP67) present in diverse eukaryotes and related to the signal peptide-binding domain of Ffh, which may well be a hitherto unrecognized component of the mitochondrial membrane protein-targeting machinery.
Keywords: LECA; Sequence Homology, Nucleic Acid; Bacterial Proteins; Receptors, Cytoplasmic and Nuclear; Ffh; sekvenční homologie nukleových kyselin; biologická evoluce; Naegleria; protists; protein targeting; signal recognition particle; genom mitochondriální; Genome, Mitochondrial; proteiny z Escherichia coli; signál-rozpoznávající částice; Biological Evolution; evolution; Escherichia coli Proteins; bakteriální proteiny; mitochondrion; receptory cytoplazmatické a nukleární; FtsY; Signal Recognition Particle